2018
DOI: 10.3390/s18092910
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Sensitivity Optical Accelerometer for Low-Frequency Vibration Measurement

Abstract: Low-frequency vibration is a harmful factor that affects the accuracy of micro/nano-measuring machines. Low-frequency vibration cannot be completely eliminated by passive control methods, such as the use of air-floating platforms. Therefore, low-frequency vibrations must be measured before being actively suppressed. In this study, the design of a low-cost high-sensitivity optical accelerometer is proposed. This optical accelerometer mainly comprises three components: a seismic mass, a leaf spring, and a sensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 30 publications
0
7
0
2
Order By: Relevance
“…According to the authors, the device was able to perform in low frequency and showed high sensitivity, and showed a resolution of 16 G at 1 Hz movement. [ 17 ]. However, its sensitivity and resolution are size dependent.…”
Section: Introductionmentioning
confidence: 99%
“…According to the authors, the device was able to perform in low frequency and showed high sensitivity, and showed a resolution of 16 G at 1 Hz movement. [ 17 ]. However, its sensitivity and resolution are size dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al [ 28 , 29 , 30 ] designed and introduced a fiber grating vibration sensor with a cantilever structure, and in order to improve the sensitivity of acceleration signal measurement, further developed an FBG acceleration sensor based on the combination of a cantilever and sliding bar. Li et al [ 31 ] put forward a low-cost and high-sensitivity optical accelerometer assembled from a seismic mass, a leaf spring, and a sensing component based on a four-quadrant photodetector (QPD). Wang et al [ 32 ] reported a MEMS acceleration sensor based on a dual-ended tuning fork resonator, which is suitable for low-frequency and low-g acceleration measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Capacitive accelerometers have much higher sensitivity and cost than piezoelectric accelerometers. The second type is the accelerometers based on optoelectronic sensors, such as fiber Bragg grating (FBG) [12]- [17], focus probe [18], [19] and position detector [20]. The sensitivity and the minimum sensing frequency of the FBG accelerometer can reach 0.362 V/g and 1 Hz respectively [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they cannot detect vibrations with a frequency less than 3 Hz and their performances have not been tested and evaluated thoroughly. In the author's previous research [20], an optical accelerometer with a four-quadrant optical detector (QPD) was developed. It performed well in detecting low frequency vibrations (as low as 0.4 Hz).…”
Section: Introductionmentioning
confidence: 99%